EIS биосенсор для определения низкой концентрации молекул ДНК - Гаспарян, Л. Ф.; Мазо, И. A.; Симонян, В. В.; Гаспарян, Ф. В. (Հայաստանի ԳԱԱ)
The results of a theoretical simulation of an electrolyte-insulator-semiconductor (EIS) biosensor made on silicon nanowire for low concentration DNA detection are presented. It is constructed equivalent electrical scheme for EIS structure. In calculations it is carry out effect concerning charge distribution in semiconductor depletion layer. The behavior and dependency of the total capacitance for EIS sensor and its capacitive sensitivity vs. DNA concentration in aqueous solution are investigated and analyzed. It is show that capacitance of an EIS sensor is very sensitive to presence of DNA molecules and sensitivity has comparatively high value at the low concentration of DNA molecules. Increasing of DNA concentration leads to decrease of EIS total capacity. It is show that one can detect and determine number of charged DNA molecules in aqueous solution by the measuring of EIS capacity changes. Capacitive sensitivity increases with growth of the gate voltage. It is shown that for the EIS biosensor threshold of sensitivity can be very low and the signal-to-noise ratio can reach high values.
Keywords: Biophysics